Public risk finance schemes in Latvia - Začeste, Ieva (Riga Graduate School of Law, 2018)
This thesis analyses the development and results of public risk finance schemes in Latvia and tries to answer the thesis question – can the national institutional framework of public risk finance schemes could be considered as successful. The thesis analyzes the historical development of the European Union and national legal framework for public risk finance schemes. It traces back the most important changes that have effected the operations of the public risk finance funds. Four generations of public risk finance scheme have so far been established in Latvia. All of them have considerably affected the development of the venture capital market. The thesis puts forward a conceptual framework for successful government venture capital programs that are able to tackle institutional aspects that have an effect on the performance of public risk finance funds.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law